Understanding the Implementation of Indonesia’s One Data Policy through Open Government Data: Evidence from Educational Institutions - Munawir Aziz (IKIP PGRI Bojonegoro, 2026)
The Indonesian government faces similar challenges in managing bureaucracy amidst technological innovation and data management, which requires strategic policy-making. This research analyses the digital government framework in the implementation of the One Data Indonesia Policy, using Open Government Data (OGD) with Innovative Resistance Theory analysis. This study seeks to examine the implementation of the One Data Policy in the Indonesian government, specifically focusing on the management of environmental education data within the Ministry of Education, Culture, Research, and Technology (2019-2024). This research will be based on these key questions: (1) How is the One Data Indonesia policy being implemented within the Ministry of Education, Culture, Research, and Technology? and (2) What challenges impede the implementation of the One Data Indonesia policy within the Ministry of Education, Culture, Research, and Technology? And (3) How can policy recommendations be formulated to develop a better strategy for the One Data Policy in Indonesia's education sector? Based on these questions, the study explores the implementation of the One Data Indonesia policy in education on government sector.